Impact of Ambience, Layout, and Lighting on Consumer Satisfaction at Fast-Food Restaurants: Moderating Role of Gender - Pokharel, Santosh; Dhodary, Shanker; Luitel, Madan Kumar; Ravi, Jaladi (Nepalese Journal of Insurance and Social Security, 2025)
Purpose: This study investigates how dimensions of the physical environment (i.e., ambience, layout, and lighting) impact consumer satisfaction in fast-food restaurants, while also assessing the moderating effect of gender.Design/methodology/approach: A cross-sectional survey was conducted among 384 patrons of fast-food restaurants in Kathmandu, Nepal, selected through convenience sampling. Data were gathered using a structured questionnaire and analyzed with SPSSv26, employing descriptive statistics, correlation, and multiple regression to examine hypothesized relationships and moderation effects.Findings: Ambience, layout, and lighting each demonstrated a positive and significant influence on consumer satisfaction, with layout emerging as the most influential factor. Contrary to initial assumptions, gender did not significantly moderate these relationships, indicating similar perceptions across male and female consumers.Conclusion: The study emphasizes that thoughtfully designed physical environments are critical drivers of consumer satisfaction, offering strategic value for sustaining competitiveness in the fast-food industry.Implications: The results provide actionable guidance for fast-food managers aiming to enhance customer satisfaction and encourage repeat visits. Emphasizing strategic layout design, alongside appealing ambience and lighting, can serve as a competitive differentiator in the crowded fast-food sector.Originality/value: Anchored in the Stimulus-Organism-Response (SOR) framework, this study contributes fresh insights by contextualizing the impact of physical environments on consumer satisfaction within Nepal’s emerging fast-food industry. It also advances understanding by explicitly testing gender as a moderating factor in this relationship.JEL Classification: M31, L83, D12, J16